Gambaran Hasil Pemeriksaan Real-Time Polymerase Chain Reaction (RT-PCR) pada Pasien yang Sudah Terkonfirmasi Positif Swab Antigen dan Reaktif Rapid Test Antibodi - Fani Nuryana Manihuruk (Herbal Medicine Journal, 2021)
Corona virus are a large family of viruses that can cause disease in humans. Examination of Real-Time Polymerase Chain Reaction (RT-PCR) is an examination using in vitro techniques for determining or measuring the extent and nature of the template DNA (DNA chain) in real time. Antigen Swab a rapid diagnostic test for Covid-19 to detect the presence of antigens from the corona virus. antibody rapid test examination is an initial screening method for detecting IgM and IgG antibodies. This research is descriptive to get an overview of the result Real-Time Polymerase Chain Reaction (RT-PCR) examination in patients who have been confirmed positive on the antigen swab and reactive on the antibody rapid test. The population in this study were patients who were confirmed positive for swab antigens totaling 183 samples and confirmed antibody reactive totaling 117 samples who underwent a follow up examination of Real-Time Polymerase Chain Reaction (RT-PCR). There were positive RT-PCR results on the antigen swab examination as many as 162 samples (88.5%) and 21 (11.5%) negative results and positive RT-PCR results on the antibody rapid test examination as many as 34 samples (29.1 %) and obtained negative results as many as 83 (70.9%). The results of this study are expected to be a science for the public in knowing supporting laboratory tests in detecting the corona virus.